Investing 101 - Kristof, Kathy. (Bloomberg Press, 2008)
"The fully updated and expanded edition of Investing 101 offers basic advice to market newcomers. Subjects include: stocks, bonds, mutual funds, retirement planning, college savings, and tax strategies. This new edition removes roadblocks and offers low-maintenance portfolios that put investors on the path to investment success"--Provided by publisher.